DESCRIPTION OF CITIZEN’S KNOWLEDGE, ATTITUDE, AND BEHAVIOR ABOUT COVID-19 VACCINATION IN A VILLAGE, EAST INDONESIA - Yedicha Nuke Manu; Angelina Alvany Damayanti; Eka Siahaan; Eva Chris Veronica Gultom; Sumiaty Aiba (Universitas Pelita Harapan, 2022)
COVID-19 is a disease that attacks the respiratory system. In October 2021, the Covid-19 death rate in Indonesia reached 143,077. Multiple efforts such as physical distancing, hands washing, mask usage, and COVID-19 vaccinations were used to reduce the number of cases. The acceptance of the COVID-19 vaccine in Indonesia depended on people’s knowledge, attitude, and behavior towards the program. The research was to identify a knowledge, attitude, and behavior of COVID-19 vaccination among people living in the Nifukani village, West Amanuban sub-district. The study used a quantitative descriptive method with a cross-sectional approach. The research sample consisted of 302 respondents. The validity test using Pearson Product Moment was declared valid with the results of r-count>r-table 0.3494. The reliability test was declared reliable with Cronbach Alpha values of 0.682 and 0.721. The data were then analyzed using univariate analysis. The results showed that the respondents had poor knowledge of Covid-19 (70.9%), good attitudes (56.3%), and good behavior (90.1%). The stakeholders, thus, had to increase people’s knowledge on Covid-19 vaccination either by leaflets, posters, or collaborating with local institutions to conduct community education. BAHASA INDONESIA ABSTRAK COVID-19 merupakan penyakit yang menyerang sistem pernapasan yang mencetak angka kematian 143.077 pada Oktober 2021 di Indonesia. Upaya yang dilakukan dalam menurunkan kejadian COVID-19 adalah menjaga jarak, mencuci tangan, menggunakan masker, dan vaksin COVID-19. Penerimaan vaksin COVID-19 di Indonesia berkaitan dengan tingkat pengetahuan, sikap, dan perilaku masyarakat terhadap program vaksinasi COVID-19. Tujuannya mengidentifikasi gambaran pengetahuan, sikap, dan perilaku masyarakat terhadap vaksinasi COVID-19 di desa Nifukani kecamatan Amanuban Barat. Penelitian menggunakan metode deskriptif kuantitatif dengan pendekatan cross-sectional. Sampel penelitian 302 responden. Uji validitas dengan Pearson Product Moment dinyatakan valid dengan hasil r-hitung>r-tabel 0,3494. Uji reliabilitas dinyatakan reliabel dengan nilai Cronbach Alpha 0,682 dan 0,721. Teknik analisa data univariat. Hasil penelitian menunjukkan bahwa responden memiliki pengetahuan tidak baik (70,9%), memiliki sikap baik (56,3%), dan perilaku baik (90,1%). Pengetahuan masyarakat perlu ditingkatkan dengan adanya kolaborasi institusi setempat dalam memberikan edukasi mengenai vaksinasi COVID-19, baik dengan leaflet, poster, maupun himbauan mengikuti sosialisasi.